Land Suitability Analysis for Relocation of Settlement Based on Natural Hazard Issues: A Case Study of the Budhigandaki Hydropower Project in Nepal - Paudel, Prakash; Sherchan, Bikash (Journal of Engineering and Sciences, 2024)
Nepal has been exposed to different hazards due to its varied topography, including the Himalayas and Terai plains. The primary objective of this research is to use remote sensing (RS) and geographic information systems (GIS) to find suitable locations in the affected former Village Development Committees (VDCs) for the relocation of people impacted by the Budhigandaki Hydroelectric Project (BGHEP). The environmental and hazard factors were used to identify suitable land for resettlement sites. The Analytical Hierarchy Process (AHP) and GIS evaluated site suitability for settlement relocation. The weights of influence factors used for site selection are determined using AHP. Four groups were created by combining weighted scores such as environmental (slope, elevation, aspect, geological formation and land cover), landslide (Topographic Wetness Index -TWI, slope, elevation, precipitation, land cover, proximity to stream, drainage density, soil and proximity to fault line), flood (TWI, slope, elevation, precipitation, land use/cover, proximity to stream and drainage density) and hazard (landslide, flood and earthquake density). Among the overall study area, the moderate susceptibility class has the largest area (78.51%), followed by low (10.91%) and high (10.58%). The results of environmental and hazard factors were combined to create a suitability index map. Four groups have been defined on the map: most suitable, suitable, less suitable, and not suitable for relocating the settlements. This study shows how the Multi-Criteria Decision Analysis (MCDA) approach can be used to identify suitable sites for relocating settlements to reduce exposure to natural hazards. The expected total land requirements for the resettlement of the households that will be displaced physically was 405 hectares. The research shows suitable locations inside the impacted VDCs, so relocation plans should be made in the most suitable locations.